Triple solutions for nonlinear elliptic problems driven by a non-homogeneous operator. (August 2020) - Bonanno, Gabriele; D'Aguì, Giuseppina; Livrea, Roberto
Abstract: Some multiplicity results for a parametric nonlinear Dirichlet problem involving a nonhomogeneous differential operator of p -Laplacian type are given. Via variational methods, the article furnishes new contributions and completes some previous results obtained for problems considering other types of differential operators and/or nonlinear terms satisfying different asymptotic conditions.